Usefulness of random skin biopsy as a diagnostic tool of intravascular lymphoma presenting with fever of unknown origin - Marinya Pongpudpunth (2018)
© 2015 Wolters Kluwer Health, Inc. Background: Intravascular B-cell lymphoma (IVBCL) is a rare type of extranodal lymphoma in which the lymphoma proliferates within vascular lumen. One of the most common presenting symptoms is prolonged fever. Although examination of a random skin biopsy from healthy-appearing skin in patients with suspected intravascular lymphoma has been reported to be useful, the sensitivity of this method for diagnosis is still unknown. Objective: To evaluate the usefulness of a random skin biopsy in the diagnosis of intravascular lymphoma in the patient presenting with fever of unknown origin. Materials and Methods: All cases that we performed random skin biopsy were retrospectively reviewed from March 2007 to June 2012 in Ramathibodi Hospital. The incisional biopsy technique was performed in 3 separate locations including 2 specimens from both upper thighs and 1 specimen from the abdomen. Results: Of the 24 cases that were consulted to dermatologist for random skin biopsy, 3 cases (13%) were diagnosed of intravascular lymphoma and all presented with prolong fever, weight loss, and remarkable deterioration in Eastern Cooperative Oncology Group (ECOG) performance status (ECOG score) > 2. Interestingly, 2 cases (8%) were diagnosed with cytophagic histiocytic panniculitis from normal-appearing skin and subsequently investigated, which leads to the diagnosed of T-cell lymphoma. Conclusions: In an elderly patient with fever of unknown origin and/or weight loss with no evident of skin lesion, markedly elevated lactate dehydrogenase, remarkable deterioration in ECOG performance status who suspected IVBCL should be consider to perform incisional random skin biopsy at least 3 specimens from both thighs and abdomen to achieve a high sensitivity. We propose that this technique may serve as an important diagnostic tool to obtain the diagnosis of IVBCL. In summary, 5 of 24 (21%) positive results from random skin biopsy helped diagnoses of lymphoma.